A Study on Gateway and Multiple Sensor Nodes Communication in IoT-Based Flood Monitoring System - Siti Balqis Zulkafli,; Faiz Asraf Saparudin, (Progress in Engineering Application and Technology, 2026)
This study describes the design and evaluation of an IoT-based flood monitoring system that uses LoRa technology to communicate between a gateway and various sensor nodes in flood-prone sections of the Muar River Basin. The goal is to determine the reliability and scalability of LoRaWAN connectivity for multi-node data transmission. A prototype system with an ultrasonic water level sensor was developed and deployed at various distances and node densities, with performance measured using Received Signal Strength Indicator (RSSI), Signal-to-Noise Ratio (SNR), and Packet Success Rate (PSR). The findings indicate that network performance degrades as transmission distance and the number of sensor nodes increase, emphasizing the importance of optimized network configuration and gateway deployment. Specifically, the results show a consistent decrease in RSSI and SNR with distance, as well as a reduction in PSR, which is attributed to path loss and packet collision as node density increases. Overall, the findings demonstrate that LoRa-based systems are suitable for flood monitoring when properly configured, with future enhancements focusing on optimizing network characteristics and expanding gateway deployment to enhance reliability and overall system performance.